Resin composition, power cable, and method for producing power cable

JP7635821B2Active Publication Date: 2025-02-26SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023502066
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-25
Filing Date
2021-11-08
Publication Date
2025-02-26
Estimated Expiration
2041-11-08

AI Technical Summary

Benefits of technology

【0011】 [本開示の効果] 本開示によれば、絶縁層の安定的な絶縁性を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635821000003
    Figure 0007635821000003
  • Figure 0007635821000001
    Figure 0007635821000001
  • Figure 0007635821000002
    Figure 0007635821000002
Patent Text Reader

Abstract

A resin composition which comprises a base resin including a polyolefin, a styrene-based elastomer including styrene units, and a copolymer comprising styrene units and maleic anhydride units, wherein the content of the copolymer is 0.5 parts by mass or higher per 100 parts by mass of the sum of the base resin and the styrene-based elastomer, the content of the styrene-based elastomer is not less than the content of the copolymer, and the copolymer contains no side chains which are eliminated by pyrolysis or hydrolysis at 300°C or lower.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin composition, a power cable, and a method for producing a power cable. This application claims priority to Japanese application "Patent Application No. 2021-28226" filed on February 25, 2021, and incorporates all of the contents of the above-mentioned Japanese application by reference. [Background technology]

[0002] In recent years, solid insulated power cables (hereinafter abbreviated as "power cables") have been developed for DC power transmission applications (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 11-16421 Summary of the Invention

[0004] According to one aspect of the present disclosure, A base resin including a polyolefin; a styrene-based elastomer containing styrene units; a copolymer comprising styrene units and maleic anhydride units; having the content of the copolymer is 0.5 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer is equal to or greater than the content of the copolymer; The copolymer does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300°C. A resin composition is provided.

[0005] According to another aspect of the present disclosure, A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer includes a resin composition having a base resin including a polyolefin, a styrene-based elastomer including a styrene unit, and a copolymer including a styrene unit and a maleic anhydride unit; a content of the copolymer in the insulating layer is 0.5 parts by mass or more when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer in the insulating layer is equal to or greater than the content of the copolymer; The copolymer does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300°C. A power cable is provided.

[0006] According to yet another aspect of the present disclosure, A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer includes a resin composition having a base resin including a polyolefin, a styrene-based elastomer including a styrene unit, and a copolymer including a styrene unit and a maleic anhydride unit; a total content of the maleic anhydride units in the insulating layer is 0.1 parts by mass or more when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer in the insulating layer is equal to or greater than the content of the copolymer; The copolymer does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300°C. A power cable is provided.

[0007] According to yet another aspect of the present disclosure, preparing a resin composition having a base resin including a polyolefin, a styrene-based elastomer including styrene units, and a copolymer including styrene units and maleic anhydride units; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, the content of the copolymer in the resin composition is 0.5 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass, The content of the styrene-based elastomer in the resin composition is equal to or greater than the content of the copolymer, The copolymer is a material that does not contain side chains that are eliminated by thermal decomposition or hydrolysis at 300°C or less. A method for manufacturing a power cable is provided.

[0008] According to yet another aspect of the present disclosure, preparing a resin composition having a base resin including a polyolefin, a styrene-based elastomer including styrene units, and a copolymer including styrene units and maleic anhydride units; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, a total content of the maleic anhydride units in the resin composition is 0.1 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass, The content of the styrene-based elastomer in the resin composition is equal to or greater than the content of the copolymer, The copolymer is a material that does not contain side chains that are eliminated by thermal decomposition or hydrolysis at 300°C or less. A method for manufacturing a power cable is provided. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view perpendicular to the axial direction of a DC power cable according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Problem that this disclosure aims to solve] An object of the present disclosure is to obtain stable insulating properties of the insulating layer.

[0011] [Effects of this disclosure] According to the present disclosure, stable insulating properties of the insulating layer can be obtained.

[0012] [Description of the embodiments of the present disclosure] <Knowledge gained by the inventors> First, the findings of the inventors will be described.

[0013] In a DC power cable, for example, space charges may be generated in the insulating layer when a high voltage is applied, which may cause the insulating properties of the insulating layer to deteriorate. (Note that the "insulating properties" of the insulating layer here refers to the volume resistivity, DC breakdown field strength, space charge characteristics, etc., and is also referred to as "DC characteristics.")

[0014] Conventionally, various measures have been attempted to suppress the accumulation of space charges in the insulation layer of DC power cables as described above. However, through intensive studies by the present inventors, it has been found that the following new problems may arise.

[0015] (i) When inorganic fillers are added In order to suppress the accumulation of space charges in the insulating layer of a DC power cable, for example, a polar inorganic filler such as carbon black or magnesium oxide (MgO) may be added to the resin composition constituting the insulating layer (for example, Patent Document 1). In this case, the insulating layer is formed, for example, by extruding the resin composition containing the inorganic filler through a mesh.

[0016] However, when such inorganic fillers are added, depending on the manufacturing conditions including the particle size, surface treatment conditions, and content of the inorganic fillers, the mesh may gradually become clogged due to aggregation of the inorganic fillers during the extrusion process of the insulating layer. If the mesh becomes clogged, the resin pressure during the extrusion process may increase. This may cause the insulation properties of the insulating layer to vary along the length of the cable, or the moldability of the insulating layer itself to decrease.

[0017] (ii) Modified polyolefin In order to suppress the accumulation of space charges in the insulation layer of a DC power cable, for example, the incorporation of organic polar groups into the resin component has been considered. As a method for incorporation of polar groups, for example, a modified polyolefin such as polyethylene modified with maleic anhydride as a polar group is added to the resin composition.

[0018] However, when modifying a polyolefin with maleic anhydride as a side chain, peroxide is required. If peroxide is used to increase the modification rate (amount of modification) of maleic anhydride, the polyolefins react with each other and gel. This may make it impossible to mold the modified polyolefin.

[0019] For the reasons mentioned above, it was difficult to increase the modification rate (modification amount) of maleic anhydride in the modified polyolefin. Therefore, it was difficult to ensure a sufficient total content of maleic anhydride in the entire resin composition. As a result, there was a possibility that local accumulation of space charge could not be suppressed. In particular, there was a tendency for the insulation property at high temperatures to be easily deteriorated.

[0020] The present disclosure is based on the above-mentioned findings of the inventors.

[0021] <Embodiments of the present disclosure> Next, embodiments of the present disclosure will be listed and described.

[0022] [1] A resin composition according to one embodiment of the present disclosure, A base resin including a polyolefin; a styrene-based elastomer containing styrene units; a copolymer comprising styrene units and maleic anhydride units; having the content of the copolymer is 0.5 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer is equal to or greater than the content of the copolymer; The copolymer does not contain any side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300°C. According to this configuration, stable insulation can be obtained.

[0023] [2] A power cable according to another aspect of the present disclosure includes: A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer includes a resin composition having a base resin including a polyolefin, a styrene-based elastomer including a styrene unit, and a copolymer including a styrene unit and a maleic anhydride unit; a content of the copolymer in the insulating layer is 0.5 parts by mass or more when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer in the insulating layer is equal to or greater than the content of the copolymer; The copolymer does not contain any side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300°C. This configuration makes it possible to obtain stable insulation properties for the insulating layer.

[0024] [3] In the power cable according to the above [2], The total content of the maleic anhydride units in the insulating layer is 0.1 parts by mass or more when the combined content of the base resin and the styrene-based elastomer is taken as 100 parts by mass. According to this structure, the maleic anhydride units can trap space charges sufficiently.

[0025] [4] A power cable according to another aspect of the present disclosure includes: A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer includes a resin composition having a base resin including a polyolefin, a styrene-based elastomer including a styrene unit, and a copolymer including a styrene unit and a maleic anhydride unit; a total content of the maleic anhydride units in the insulating layer is 0.1 parts by mass or more when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer in the insulating layer is equal to or greater than the content of the copolymer; The copolymer does not contain any side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300°C. This configuration makes it possible to obtain stable insulation properties for the insulating layer.

[0026] [5] In the power cable according to any one of [2] to [4] above, The copolymer does not contain any ester, ether, amide, urethane or siloxane linkages. This configuration makes it possible to obtain stable insulation properties for the insulating layer.

[0027] [6] The power cable according to any one of [2] to [5] above, The volume resistivity of the insulating layer measured under conditions of a temperature of 90° C. and a DC electric field of 75 kV / mm was 1.0×10 15 Ω·cm or more. This configuration enables stable DC power transmission.

[0028] [7] In the power cable according to any one of [2] to [6] above, The amount of space charge accumulation in the insulating layer sheet measured under conditions of a temperature of 90° C. and a DC electric field of 75 kV / mm is 100% or less. This configuration enables stable DC power transmission.

[0029] [8] The power cable according to any one of [2] to [7] above, The content of the copolymer is less than 20 parts by mass when the total content of the base resin and the styrene-based elastomer is taken as 100 parts by mass. According to this configuration, deformation at high temperatures can be suppressed.

[0030] [9] The power cable according to the above [7] or [8], The thermal deformation rate of the insulating layer measured under conditions of a temperature of 120° C. and a load of 2 kg is 40% or less. According to this configuration, the heat resistance of the power cable can be improved even in a high-temperature state.

[0031]

[10] The power cable according to any one of [2] to [9] above, The content of the inorganic compound in the insulating layer is less than 0.01 part by mass when the total content of the base resin and the styrene-based elastomer is taken as 100 parts by mass. According to this configuration, clogging of the mesh can be suppressed in the extrusion process of the insulating layer.

[0032]

[11] The power cable according to any one of [2] to [9] above, The insulating layer further contains less than 1 part by mass of an inorganic filler when the total content of the base resin and the styrene-based elastomer is 100 parts by mass. According to this configuration, clogging of the mesh during the extrusion process can be suppressed, and the effect of improving the insulation properties of the insulating layer can be stably obtained.

[0033]

[12] The power cable according to the above

[10] or

[11] , The insulating layer satisfies the following formula (1) for the rate of variation of DC breakdown strength: (E MAX -E MIN ) / E AVE ≦0.2 (1) However, the DC breakdown strength is the electric field strength at the time when a DC electric field is applied to each of a plurality of sheets taken from a plurality of locations of the insulating layer at predetermined intervals in the longitudinal direction of the conductor at a temperature of 90° C. and the sheet undergoes dielectric breakdown; E MAX , E MIN and E AVE are the maximum, minimum and average DC breakdown strengths of the sheets, respectively. According to this configuration, stable insulation properties can be obtained for the entire long power cable.

[0034]

[13] The power cable according to any one of [2] to

[12] above, The copolymer has a glass transition temperature of 110° C. or higher. With this configuration, the mechanical properties of the power cable can be ensured.

[0035]

[14] The power cable according to any one of [2] to

[13] above, The copolymer has a glass transition temperature of 140° C. or less. This configuration makes it possible to prevent the copolymer (C) from becoming glassy (filler-like).

[0036]

[15] A method for producing a power cable according to yet another aspect of the present disclosure includes: preparing a resin composition having a base resin including a polyolefin, a styrene-based elastomer including styrene units, and a copolymer including styrene units and maleic anhydride units; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, the content of the copolymer in the resin composition is 0.5 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass, The content of the styrene-based elastomer in the resin composition is equal to or greater than the content of the copolymer, The copolymer is a material that does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures of 300° C. or less. According to this configuration, a power cable having an insulating layer with stable insulating properties can be obtained.

[0037]

[16] A method for producing a power cable according to yet another aspect of the present disclosure includes: preparing a resin composition having a base resin including a polyolefin, a styrene-based elastomer including styrene units, and a copolymer including styrene units and maleic anhydride units; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, a total content of the maleic anhydride units in the resin composition is 0.1 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass, The content of the styrene-based elastomer in the resin composition is equal to or greater than the content of the copolymer, The copolymer is a material that does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures of 300° C. or less. According to this configuration, a power cable having an insulating layer with stable insulating properties can be obtained.

[0038] [Details of the embodiment of the present disclosure] Next, an embodiment of the present disclosure will be described below with reference to the drawings. Note that the present disclosure is not limited to these examples, but is defined by the claims, and is intended to include all modifications within the meaning and scope of the claims.

[0039] <One embodiment of the present disclosure> (1) Resin composition The resin composition of the present embodiment is a material constituting the insulating layer 130 of the power cable 10 described below. The resin composition contains, for example, a base resin (A), a styrene-based elastomer (B), a copolymer (C), and other additives. Hereinafter, the base resin (A) will also be referred to as the "(A) component", the styrene-based elastomer (B) as the "(B) component", and the copolymer (C) as the "(C) component".

[0040] [Base resin (A)] The base resin (base polymer) refers to the resin component that constitutes the main component of a resin composition. The "main component" refers to the component that is contained in the largest amount.

[0041] The base resin of the present embodiment contains, for example, polyolefin. Examples of polyolefins constituting the base resin include polyethylene, polypropylene, ethylene-α-olefin copolymers, and thermoplastic elastomers (non-styrene elastomers) in which ethylene-propylene rubber is dispersed or copolymerized in polypropylene. Among these, polyethylene or polypropylene is preferred. Two or more of these may be used in combination.

[0042] Examples of the polyethylene constituting the base resin include low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), etc. Furthermore, these polyethylenes may be, for example, either linear or branched.

[0043] Examples of polypropylene constituting the base resin include propylene homopolymers (homopolypropylenes) and propylene random polymers (random polypropylenes). The stereoregularity is not limited, but is preferably isotactic, for example.

[0044] When the resin composition contains the above-mentioned base resin (A), the basic properties and mechanical properties of the power cable 10 can be ensured.

[0045] The elastic modulus of the polyolefin measured by a scanning probe microscope (SPM) is preferably, for example, 300 MPa or more and 2000 MPa or less. The elastic modulus measurement by SPM is performed at 25° C. under the condition that a cantilever having a tip made of silicon and a curvature radius of less than 20 nm is used to tap the polyolefin 60,000 times within a 10 μm square area. When the elastic modulus of the polyolefin is within the above-mentioned range, the flexibility and rigidity of the power cable 10 can be achieved at the same time.

[0046] [Styrene-based elastomer (B)] The styrene-based elastomer (B) contains, for example, at least a styrene unit as a monomer unit.

[0047] By including the styrene unit in the styrene elastomer (B), the compatibility between the styrene elastomer (B) and the copolymer (C) including the styrene unit described below can be improved. In other words, the copolymer (C) can be uniformly dispersed in the base resin (A) with the styrene elastomer (B) interposed therebetween. This makes it easy to increase the content of the copolymer (C) in the resin composition.

[0048] In addition, since the styrene elastomer (B) contains styrene units, space charges can be trapped not only in the maleic anhydride units in the copolymer (C) described below, but also in the aromatic rings of the styrene units in the styrene elastomer (B), thereby making it possible to suppress local accumulation of space charges.

[0049] The styrene-based elastomer (B) is, for example, a copolymer containing a styrene unit as a hard segment and at least one monomer unit of ethylene, propylene, butylene, isoprene, etc. as a soft segment.

[0050] Examples of the styrene-based elastomer (B) include styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer, styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-isoprene-styrene copolymer (SIS), hydrogenated styrene-isoprene-styrene copolymer, hydrogenated styrene-butadiene rubber, hydrogenated styrene-isoprene rubber, styrene-ethylene-butylene olefin crystalline block copolymer, etc. Two or more of these may be used in combination.

[0051] In this context, "hydrogenated" means that hydrogen has been added to the double bond. For example, "hydrogenated styrene butadiene styrene block copolymer" means a polymer in which hydrogen has been added to the double bond of a styrene butadiene styrene block copolymer. No hydrogen has been added to the double bond of the aromatic ring of styrene. "Hydrogenated styrene butadiene styrene block copolymer" can be rephrased as styrene ethylene butylene styrene block copolymer (SEBS).

[0052] When the base resin contains polyethylene, it is preferable that the styrene-based elastomer (B) contains, for example, an ethylene unit among the above-mentioned materials, so that the compatibility between the base resin (A) and the styrene-based elastomer (B) can be improved.

[0053] The content of ethylene units in the styrene-based elastomer (B) (hereinafter simply referred to as "ethylene content") is not particularly limited, but is preferably, for example, 10% by mass or more and 50% by mass or less. By making the ethylene content 10% by mass or more, it is possible to sufficiently improve the compatibility between the base resin (A) and the styrene-based elastomer (B). On the other hand, by making the ethylene content 50% by mass or less, it is possible to ensure a predetermined amount of styrene units. This makes it possible to sufficiently improve the compatibility between the styrene-based elastomer (B) and the copolymer (C) described below, and as a result, it is possible to stably improve the insulating properties at high temperatures.

[0054] Among the above-mentioned materials, hydrogenated materials that do not contain double bonds in the chemical structure except for aromatic rings are preferred. When non-hydrogenated materials are used, the resin components may be thermally deteriorated during molding of the resin composition, and the properties of the resulting molded product may be deteriorated. In contrast, the use of hydrogenated materials can improve resistance to thermal deterioration. This allows the properties of the molded product to be maintained at a higher level.

[0055] Moreover, the styrene-based elastomer (B) has a low elastic modulus. Specifically, the elastic modulus of the styrene-based elastomer (B) measured by SPM is preferably, for example, 10 MPa or more and 400 MPa or less. The measurement conditions are the same as those described for the base resin (A). By making the elastic modulus of the styrene-based elastomer (B) 10 MPa or more, the insulating layer 130 can be stably molded. On the other hand, by making the elastic modulus of the styrene-based elastomer (B) 400 MPa or less, the flexibility of the power cable 10 can be improved.

[0056] The styrene elastomer (B) has low crystallinity. Specifically, the styrene elastomer (B) does not have a melting point or has a melting point of less than 100° C. The heat of fusion of the styrene elastomer (B) is, for example, 50 J / g or less, preferably 30 J / g or less.

[0057] In addition, styrene-modified polyethylene is not suitable as the styrene-based elastomer (B) in this embodiment. This is because, in order to suppress local accumulation of space charges (to exhibit good DC characteristics), it is necessary to finely disperse the copolymer (C) described below in the composition. However, with styrene-modified polyethylene, it is difficult to ensure a predetermined amount of grafted styrene units. For example, in styrene-grafted polyethylene in which 0.1 mass % to 10 mass % of styrene is grafted, the styrene units are insufficient. For this reason, it is difficult to improve the compatibility between the styrene-based elastomer (B) and the copolymer (C) described below. As a result, the dispersibility of the copolymer (C) may decrease.

[0058] The content of the styrene-based elastomer (B) in the resin composition is, for example, equal to or greater than the content of the copolymer (C) described below. If the content of the (B) component is less than the content of the (C) component, the styrene-based elastomer (B) cannot be sufficiently interposed in the base resin (A), and it becomes difficult to uniformly disperse the copolymer (C). For this reason, it may not be possible to suppress local accumulation of space charges. In particular, the insulating properties at high temperatures may be reduced. In contrast, in this embodiment, by setting the content of the (B) component to be equal to or greater than the content of the (C) component, it is possible to uniformly disperse the copolymer (C) in the base resin (A) while sufficiently interposing the styrene-based elastomer (B). This makes it possible to suppress local accumulation of space charges. In particular, it is possible to improve the insulating properties at high temperatures.

[0059] The upper limit of the content of the styrene-based elastomer (B) in the resin composition is not limited. However, the content of the styrene-based elastomer (B) is, for example, 40 parts by mass or less, preferably 30 parts by mass or less, when the total content of the (A) component and the (B) component is 100 parts by mass. In other words, the content of the base resin (A) is 60 parts by mass or more, preferably 70 parts by mass or more. This makes it possible to stably ensure the basic characteristics and mechanical characteristics of the power cable 10.

[0060] [Copolymer (C)] The copolymer (C) contains, for example, a styrene unit and a maleic anhydride unit as monomer units. In this way, by incorporating a maleic anhydride unit as one monomer unit constituting the main chain into the copolymer (C) containing a styrene unit, the molecular design of the copolymer (C) can be freely performed. This makes it possible to easily increase the content of maleic anhydride units in one molecule. As a result, the total content of maleic anhydride units in the entire resin composition can be increased.

[0061] Moreover, the copolymer (C) does not include a side chain that is detached by thermal decomposition or hydrolysis at, for example, 300°C or less. Here, the "side chain that is detached by thermal decomposition or hydrolysis at, for example, 300°C or less" refers to a side chain that may be detached from the main chain at least in at least one of the extrusion process, crosslinking process, and installation environment in which the insulating layer 130 may absorb moisture. By not including such a side chain in the copolymer (C), even if the resin composition is exposed to high temperature or high humidity in the extrusion process, crosslinking process, and high humidity installation environment, the detachment of the side chain can be suppressed, and the generation of low molecular weight components caused by the side chain can be suppressed. This makes it possible to suppress the accumulation of space charge in the low molecular weight components.

[0062] Specifically, it is preferable that the copolymer (C) does not contain any of, for example, ester, ether, amide, urethane, and siloxane bonds, which, if present as side chains, may be eliminated by thermal decomposition or hydrolysis at temperatures of 300° C. or lower.

[0063] Examples of the monomer unit containing a side chain that is eliminated by thermal decomposition or hydrolysis at 300° C. or less include vinyl acetate, allyl ether, and acrylamide.

[0064] On the other hand, examples of the monomer units not containing the above-mentioned eliminable side chain, that is, other monomer units which may be contained in the copolymer (C), include olefins, styrene, maleic anhydride, and the like.

[0065] Also, it is preferable that the copolymer (C) does not have any polar groups other than the maleic anhydride units, for example, so that the generation of low molecular weight components due to polar groups other than the maleic anhydride units can be suppressed.

[0066] Furthermore, it is more preferable that the copolymer (C) is composed of, for example, only styrene units and maleic anhydride units. In other words, it is more preferable that the copolymer (C) is a styrene-maleic anhydride copolymer. That is, by eliminating monomer units other than these in the copolymer (C), the content of maleic anhydride units in one molecule can be increased. As a result, the total content of maleic anhydride units in the entire resin composition can be easily increased.

[0067] The content of the styrene unit in the copolymer (C) (hereinafter, simply referred to as "styrene content") is preferably, for example, 50% by mass or more and 90% by mass or less. If the styrene content is less than 50% by mass, the compatibility between the copolymer (C) and the styrene-based elastomer (B) may decrease. On the other hand, by making the styrene content 50% by mass or more, the compatibility between the copolymer (C) and the styrene-based elastomer (B) can be improved. On the other hand, if the styrene content exceeds 90% by mass, the insulating layer 130 may easily become flexible and deform under high temperature conditions. If the styrene content exceeds 90% by mass, it becomes difficult to secure a predetermined amount of maleic anhydride units. On the other hand, by making the styrene content 90% by mass or less, it is possible to suppress excessive flexibility and excessive deformation of the insulating layer 130 under high temperature conditions. In other words, it is possible to secure mechanical properties. Also, by making the styrene content 90% by mass or less, it is possible to secure a predetermined amount of maleic anhydride units. The total content of maleic anhydride units in the resin composition will be described later.

[0068] On the other hand, the content of maleic anhydride units in the copolymer (C) (hereinafter also simply referred to as "maleic anhydride content") is preferably, for example, 10% by mass or more and 50% by mass or less. By making the maleic anhydride content 10% by mass or more, the total content of maleic anhydride units in the resin composition can be ensured. The total content of maleic anhydride units in the resin composition will be described later. On the other hand, by making the maleic anhydride content 50% by mass or less, a predetermined amount of styrene units can be ensured. This can improve the compatibility between the copolymer (C) and the styrene-based elastomer (B).

[0069] The copolymer (C) may contain a predetermined amount of monomer units other than the styrene unit and the maleic anhydride unit.

[0070] The glass transition temperature of the copolymer (C) is, for example, equal to or higher than 110° C. This makes it possible to prevent the power cable 10 from becoming excessively flexible, thereby ensuring the mechanical properties of the power cable 10.

[0071] On the other hand, the glass transition temperature of the copolymer (C) is, for example, 140° C. or lower. This makes it possible to prevent the copolymer (C) from becoming glassy (filler-like) even under the processing temperature conditions in the extrusion process of the insulating layer 130, and to prevent local aggregation of the copolymer (C). As a result, the copolymer (C) can be uniformly dispersed throughout the insulating layer 130.

[0072] Moreover, the elastic modulus of the copolymer (C) measured by SPM is preferably, for example, 1300 MPa or more and 3000 MPa or less. The measurement conditions are the same as those described for the base resin (A). By making the elastic modulus of the copolymer (C) 1300 MPa or more, rigidity can be ensured. On the other hand, by making the elastic modulus of the copolymer (C) 3000 MPa or less, flexibility can be ensured.

[0073] In this embodiment, the content of the copolymer (C) in the resin composition is high, that is, the total content of maleic anhydride units in the resin composition is higher than in the past.

[0074] Specifically, the content of the copolymer (C) in the resin composition is, for example, 0.5 parts by mass or more, preferably 4 parts by mass or more, when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. If the content of the copolymer (C) is less than 0.5 parts by mass, it is difficult to ensure a sufficient total content of maleic anhydride units in the resin composition. Therefore, there is a possibility that the space charge cannot be sufficiently trapped in the maleic anhydride units. On the other hand, by making the content of the copolymer (C) 0.5 parts by mass or more, the total content of the maleic anhydride units in the resin composition can be sufficiently ensured. This allows the space charge to be sufficiently trapped in the maleic anhydride units. Furthermore, by making the content of the copolymer (C) 4 parts by mass or more, the space charge can be stably trapped in the maleic anhydride units.

[0075] The total content of the maleic anhydride units in the resin composition is, for example, 0.1 parts by mass or more, preferably 0.8 parts by mass or more, when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. This allows the maleic anhydride units to adequately trap space charges, as described above. As a result, the insulating layer 130 can have stable insulating properties. The insulating properties of the insulating layer 130 will be described in detail later.

[0076] On the other hand, in this embodiment, the content of the copolymer (C) in the resin composition is prevented from becoming excessive.

[0077] Specifically, the content of the copolymer (C) in the resin composition is less than 20 parts by mass, and preferably 15 parts by mass or less, when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. When the content of the copolymer (C) is 20 parts by mass or more, the contribution of the styrene units in the copolymer (C) to deformation increases. As a result, the power cable 10 is easily deformed at high temperatures. On the other hand, by making the content of the copolymer (C) less than 20 parts by mass, the contribution of the styrene units in the copolymer (C) to deformation can be reduced. As a result, the deformation of the power cable 10 at high temperatures can be suppressed. Furthermore, by making the content of the copolymer (C) 15 parts by mass or less, the deformation of the power cable 10 at high temperatures can be stably suppressed.

[0078] [Other additives] The resin composition of the present embodiment may contain the following materials as other additives.

[0079] [Crosslinking agent] The crosslinking agent is, for example, an organic peroxide. Examples of the organic peroxide include dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)benzene, etc. Two or more of these may be used in combination.

[0080] When the resin composition contains a crosslinking agent, the content of the crosslinking agent is not limited. However, the content of the crosslinking agent is preferably 0.5 parts by mass or more and 3.0 parts by mass or less when the total content of the (A) component and the (B) component is 100 parts by mass. By making the content of the crosslinking agent 3.0 parts by mass or less, resistance to scorch can be ensured.

[0081] [Antioxidants] Examples of the antioxidant include 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,4-bis-[(octylthio)methyl]-o-cresol, 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, bis[2-methyl-4-{3-n-alkyl(C12 or C14)thiopropionyloxy}-5-t-butylphenyl]sulfide, and 4,4'-thiobis(3-methyl-6-t-butylphenol). Two or more of these may be used in combination.

[0082] When the resin composition contains an antioxidant, the content of the antioxidant is not limited, but is preferably 0.1 parts by mass or more and 0.5 parts by mass or less when the total content of the (A) component and the (B) component is taken as 100 parts by mass.

[0083] [Lubricant] The lubricant acts to improve the fluidity of the resin composition in the extrusion process of the insulating layer 130. The lubricant in this embodiment is, for example, a fatty acid metal salt or a fatty acid amide. Examples of the fatty acid metal salt include magnesium stearate, zinc stearate, aluminum stearate, magnesium montanate, and the like. Examples of the fatty acid amide include oleic acid amide or stearic acid amide. Two or more of these may be used in combination.

[0084] When the resin composition contains a lubricant, the content of the lubricant is not limited, but is preferably 0.01 parts by mass or more and 0.5 parts by mass or less when the total content of the (A) component and the (B) component is 100 parts by mass.

[0085] The resin composition may further contain, for example, a colorant.

[0086] On the other hand, the resin composition of the present embodiment does not contain inorganic compounds such as inorganic fillers. The term "inorganic compounds" used here means compounds other than organic compounds containing organic substituents, and does not include the above-mentioned fatty acid metal salts. That is, inorganic fillers and the like that are added to the insulating layer for general DC power cables are not intentionally mixed into the resin composition of the present embodiment, and inorganic compounds are hardly contained. Even if an inorganic compound is contained in the resin composition of the present embodiment, it is only a trace amount of the inorganic compound as an inevitable impurity in the resin composition. Specifically, the content of the inorganic compound contained in the resin composition is less than 0.01 parts by mass when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. This makes it possible to suppress clogging of the mesh in the extrusion process of the insulating layer 130.

[0087] (2) DC power cable Next, the DC power cable of this embodiment will be described with reference to Fig. 1. Fig. 1 is a cross-sectional view perpendicular to the axial direction of the DC power cable according to this embodiment.

[0088] The power cable 10 of this embodiment is configured as a so-called solid insulated DC power cable, and has, for example, a conductor 110, an inner semiconductive layer 120, an insulating layer 130, an outer semiconductive layer 140, a shielding layer 150, and a sheath 160.

[0089] (Conductor (conductive part)) The conductor 110 is formed by twisting together a plurality of conductor core wires (conductive core wires) made of, for example, pure copper, a copper alloy, aluminum, an aluminum alloy, or the like.

[0090] (internal semiconductive layer) The internal semiconductive layer 120 is provided so as to cover the outer periphery of the conductor 110. The internal semiconductive layer 120 has semiconductivity and is configured to suppress electric field concentration on the surface side of the conductor 110. The internal semiconductive layer 120 contains, for example, at least one of ethylene-based copolymers such as ethylene-ethyl acrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-vinyl acetate copolymer, olefin-based elastomer, and the above-mentioned low crystalline resin, and conductive carbon black.

[0091] (insulating layer) The insulating layer 130 is provided so as to cover the outer periphery of the internal semiconductive layer 120. The insulating layer 130 contains the resin composition of this embodiment described above.

[0092] When the insulating layer 130 of this embodiment is cross-linked by a cross-linking agent, at least a portion of the base resin (A), the styrene-based elastomer (B), and the copolymer (C) are cross-linked. Note that the (A) component, the (B) component, and the copolymer (C) may have remaining portions that are not cross-linked.

[0093] (Outer semiconducting layer) The outer semiconductive layer 140 is provided so as to cover the outer periphery of the insulating layer 130. The outer semiconductive layer 140 has semiconductivity and is configured to suppress electric field concentration between the insulating layer 130 and the shielding layer 150. The outer semiconductive layer 140 is configured, for example, from the same material as the inner semiconductive layer 120.

[0094] (shielding layer) The shielding layer 150 is provided so as to cover the outer periphery of the outer semiconductive layer 140. The shielding layer 150 is formed, for example, by winding a copper tape, or is formed as a wire shield in which a plurality of soft copper wires or the like are wound. Note that a tape made of a material such as a rubber-coated cloth may be wound on the inside or outside of the shielding layer 150.

[0095] (sheath) The sheath 160 is provided so as to cover the outer periphery of the shielding layer 150. The sheath 160 is made of, for example, polyvinyl chloride or polyethylene.

[0096] (Insulating properties of insulating layer) In this embodiment, since the insulating layer 130 is made of the above-mentioned resin composition, stable insulating properties are obtained.

[0097] Specifically, the insulating layer 130 of this embodiment satisfies the following insulating requirements measured, for example, under high temperature and high electric field conditions. The measurement is performed, for example, on a sheet taken from the center in the thickness direction of the insulating layer 130. The sheet thickness of the insulating layer 130 at this time is, for example, 0.2 mm.

[0098] The volume resistivity of the sheet of the insulating layer 130 measured under conditions of a temperature of 90° C. and a DC electric field of 50 kV / mm is, for example, 1.0×10 15 Ω cm or more, preferably 1.0×10 16 Ω·cm or more.

[0099] Furthermore, the amount of space charge accumulation in the sheet of insulating layer 130 measured under conditions of a temperature of 90° C. and a DC electric field of 50 kV / mm is, for example, 100% or less, and preferably 25% or less.

[0100] However, the amount of space charge accumulation is determined by the current integral charge method. In this method, charge is accumulated in a measuring capacitor connected in series to the sheet as a sample, and the amount of charge, which is the integral value of the current, is evaluated. Specifically, a DC electric field of 50 kV / mm is continuously applied to the sample at a temperature of 90°C, and the amount of charge Q after 300 seconds has elapsed is 300 Based on the charge amount Q0 immediately after application (0 seconds), the amount of space charge accumulation is calculated using the following formula. Space charge accumulation amount = (Q 300 / Q0-1)×100

[0101] The insulating layer 130 of this embodiment satisfies the following insulating requirements even under severer electric field conditions, for example.

[0102] The volume resistivity of the sheet of the insulating layer 130 measured under conditions of a temperature of 90° C. and a DC electric field of 75 kV / mm was 1.0×10 15 Ω cm or more, preferably 1.0×10 16 Ω·cm or more.

[0103] Moreover, the amount of space charge accumulation in the sheet of insulating layer 130 measured under conditions of a temperature of 90° C. and a DC electric field of 75 kV / mm is 100% or less, and preferably 25% or less.

[0104] (shape stability) Furthermore, the insulating layer 130 of this embodiment satisfies the following requirements for shape stability under high temperature conditions, for example.

[0105] The thermal deformation rate of the insulating layer 130 measured in accordance with JIS C3005 under conditions of a temperature of 120° C. and a load of 2 kg is 40% or less.

[0106] (Extrusion stability: insulation in the longitudinal direction) Furthermore, the insulating layer 130 of this embodiment satisfies the requirement of uniform insulation along its length by suppressing clogging of the mesh during the extrusion process.

[0107] Specifically, the insulating layer 130 satisfies, for example, the following formula (1) for the rate of variation of the DC breakdown strength. (E MAX -E MIN ) / E AVE ≦0.2 (1)

[0108] Here, the DC breakdown strength is the electric field strength at which a DC electric field is applied to each of a plurality of sheets taken from a plurality of locations of the insulating layer 130 at a predetermined interval in the length direction of the conductor 110 at a temperature of 90° C., causing dielectric breakdown in the sheet. MAX , E MIN and E AVE are the maximum, minimum and average DC breakdown strengths of the sheets, respectively.

[0109] (Specific dimensions, etc.) Although there are no particular limitations on the specific dimensions of the power cable 10, for example, the diameter of the conductor 110 is 5 mm or more and 75 mm or less, the thickness of the inner semiconductive layer 120 is 0.5 mm or more and 3 mm or less, the thickness of the insulating layer 130 is 1 mm or more and 35 mm or less, the thickness of the outer semiconductive layer 140 is 0.5 mm or more and 3 mm or less, the thickness of the shielding layer 150 is 1 mm or more and 5 mm or less, and the thickness of the sheath 160 is 1 mm or more. The DC voltage applied to the power cable 10 of this embodiment is, for example, 20 kV or more.

[0110] (3) Manufacturing method of DC power cable Next, a method for manufacturing the DC power cable according to the present embodiment will be described. Hereinafter, steps are abbreviated as "S".

[0111] (S100: Resin composition preparation step) First, a resin composition is prepared which has a base resin (A) containing a polyolefin, a styrene-based elastomer (B) containing a styrene unit, and a copolymer (C) containing a styrene unit and a maleic anhydride unit.

[0112] The base resin (A), the styrene-based elastomer (B), the copolymer (C), and other additives are mixed (kneaded) in a mixer such as a Banbury mixer or a kneader to form a mixture. After the mixture is formed, the mixture is granulated in an extruder. This forms a pellet-shaped resin composition that will form the insulating layer 130. Note that the steps from mixing to granulation may be performed in one go using a twin-screw extruder that has a high kneading effect.

[0113] In this embodiment, the content of the copolymer (C) in the resin composition is 0.5 parts by mass or more and less than 20 parts by mass when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass.

[0114] Alternatively, the total content of the maleic anhydride units in the resin composition may be 0.1 parts by mass or more and less than 4 parts by mass when the combined content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass.

[0115] In this embodiment, the content of the styrene-based elastomer (B) in the resin composition is set to be equal to or greater than the content of the copolymer (C).

[0116] In this embodiment, the copolymer (C) is a material that does not contain a side chain that is eliminated by thermal decomposition or hydrolysis at 300° C. or lower.

[0117] (S200: Conductor preparation process) On the other hand, conductor 110 is prepared by twisting together a plurality of conductor core wires.

[0118] (S300: Cable core forming process (extrusion process)) Next, a resin composition for the internal semiconductive layer, for example, a pre-mix of an ethylene-ethyl acrylate copolymer and conductive carbon black, is fed into extruder A, which forms the internal semiconductive layer 120, of the three-layer co-extruder.

[0119] The above-mentioned pellet-shaped resin composition is fed into extruder B which forms insulating layer 130 .

[0120] A resin composition for an outer semiconductive layer, which is made of the same materials as the resin composition for an inner semiconductive layer charged in extruder A, is charged in extruder C for forming the outer semiconductive layer 140 .

[0121] Next, the extrudates from the extruders A to C are guided to a common head, and the inner semiconductive layer 120, the insulating layer 130 and the outer semiconductive layer 140 are simultaneously extruded from the inside to the outside around the periphery of the conductor 110.

[0122] In this embodiment, the insulating layer 130 is then cross-linked in a bridging tube pressurized with nitrogen gas or the like by heating through radiation from an infrared heater or by heat transfer through a heat medium such as high-temperature nitrogen gas or silicone oil. This forms a cable core composed of the conductor 110, the inner semiconductive layer 120, the insulating layer 130, and the outer semiconductive layer 140.

[0123] (S400: Shielding layer formation process) Next, a shielding layer 150 is formed on the outside of the outer semiconducting layer 140 by winding, for example, a copper tape.

[0124] (S500: Sheath forming process) Next, vinyl chloride is put into an extruder and extruded to form a sheath 160 around the outer periphery of the shielding layer 150 .

[0125] In this manner, the power cable 10 is manufactured as a solid insulated DC power cable.

[0126] (4) Effects of this embodiment According to this embodiment, one or more of the following advantages are achieved.

[0127] (a) In this embodiment, the resin composition constituting the insulating layer 130 includes a base resin (A) containing polyolefin, a styrene-based elastomer (B) containing a styrene unit, and a copolymer (C) containing a styrene unit and a maleic anhydride unit. By incorporating a maleic anhydride unit as one monomer unit constituting the main chain into the copolymer (C) containing a styrene unit, the copolymer (C) can be freely molecular designed. This makes it possible to easily increase the content of maleic anhydride units in one molecule. By mixing the copolymer (C) with the base resin (A) together with the above-mentioned styrene-based elastomer (B), it is possible to increase the total content of maleic anhydride units in the entire insulating layer 130 while dispersing maleic anhydride uniformly in the insulating layer 130. This makes it possible to trap space charges in the maleic anhydride units as polar groups uniformly dispersed in the insulating layer 130. That is, it is possible to suppress local accumulation of space charges in the insulating layer 130.

[0128] In this way, by suppressing the local accumulation of space charge, it is possible to obtain stable insulation properties of the insulating layer 130. Specifically, it is possible to make the insulating layer 130 withstand high voltage even at high temperatures. As a result, the power cable 10 of this embodiment enables stable DC transmission.

[0129] (b) The content of the copolymer (C) in the resin composition (i.e., in the insulating layer 130) is 0.5 parts by mass or more when the total content of the base resin (A) and the styrene-based elastomer (B) is taken as 100 parts by mass. This makes it possible to easily ensure the total content of maleic anhydride units in the insulating layer 130. Specifically, the total content of maleic anhydride units in the resin composition can be set to 0.1 parts by mass or more.

[0130] By making the total content of the maleic anhydride units 0.1 parts by mass or more, the maleic anhydride units can trap space charges sufficiently, which allows the insulating layer 130 to have a high withstand voltage even at high temperatures.

[0131] (c) The content of the styrene-based elastomer (B) in the resin composition (i.e., in the insulating layer 130) is equal to or greater than the content of the copolymer (C). This allows the copolymer (C) to be uniformly dispersed in the base resin (A) while the styrene-based elastomer (B) is sufficiently interposed therebetween. As a result, localized accumulation of space charge can be suppressed. As described above, the insulating properties can be improved, particularly at high temperatures.

[0132] (d) The copolymer (C) does not contain any side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300°C.

[0133] Here, let us consider the case where the copolymer (C) contains a side chain that is eliminated by thermal decomposition or hydrolysis at high temperature. In this case, when the resin composition is exposed to high temperature or high humidity in at least one of the extrusion process, the crosslinking process, and the installation environment where the insulating layer may absorb moisture, the side chain is eliminated, and low molecular weight components due to the side chain are generated in the insulating layer. When such low molecular weight components are generated, space charges are locally accumulated in the low molecular weight components in the insulating layer. In other words, even if the maleic anhydride units as the polar groups of the above-mentioned copolymer (C) are dispersed, there is a possibility that there will be some parts where the space charge trapping effect of the dispersed maleic anhydride cannot be obtained.

[0134] In contrast, in the present embodiment, since the copolymer (C) does not contain the above-mentioned side chains, even if the resin composition is exposed to high temperatures in the extrusion process and crosslinking process, the detachment of the side chains can be suppressed, and the generation of low molecular weight components due to the side chains can be suppressed. As a result, the accumulation of space charges in the low molecular weight components can be suppressed. In other words, it is possible to uniformly obtain the space charge trapping effect of the dispersed maleic anhydride.

[0135] (e) The content of the copolymer (C) in the resin composition (i.e., in the insulating layer 130) is less than 20 parts by mass when the total content of the base resin (A) and the styrene-based elastomer (B) is taken as 100 parts by mass. This makes it possible to reduce the contribution of the styrene units in the copolymer (C) to deformation. As a result, it is possible to suppress deformation of the power cable 10 at high temperatures. In other words, it is possible to improve the heat resistance even in the shape of the power cable 10 at high temperatures.

[0136] (f) In this embodiment, the insulating layer 130 does not contain an inorganic compound such as an inorganic filler. Specifically, the content of the inorganic compound in the insulating layer 130 is less than 0.01 parts by mass when the total content of the base resin (A) and the styrene-based elastomer (B) is taken as 100 parts by mass. This makes it possible to suppress clogging of the mesh during the extrusion process of the insulating layer 130.

[0137] In the extrusion process of the insulating layer 130, clogging of the mesh can be suppressed, thereby suppressing the variation in the insulating properties of the insulating layer 130 in the length direction of the conductor 110. In addition, deterioration in the formability of the insulating layer 130 itself can be suppressed.

[0138] As a result, a long power cable can be manufactured in a continuous extrusion process, and stable insulation properties can be obtained for the entire long power cable.

[0139] (5) Modifications of an embodiment of the present disclosure The above-described embodiment can be modified as required, as in the following modified examples. Hereinafter, only elements different from the above-described embodiment will be described, and descriptions of elements substantially identical to those described in the above-described embodiment will be omitted.

[0140] [Variation 1] In the first modification, the base resin (A) may further contain, for example, a maleic anhydride-modified polyolefin in which maleic anhydride is grafted to a polyolefin.

[0141] The polyolefin constituting the maleic anhydride-modified polyolefin is, for example, the same as the other polyolefins contained in the base resin (A). Specifically, the polyolefin constituting the maleic anhydride-modified polyolefin is, for example, polyethylene.

[0142] The modification rate (copolymerization rate) of maleic anhydride to polyolefin in the maleic anhydride-modified polyolefin is not particularly limited, but is, for example, 0.1% to 5%. By setting the modification rate of maleic anhydride to polyolefin to 0.1% or more, the compatibility between the base resin (A) and the copolymer (C) can be improved, and the copolymer (C) can be uniformly dispersed. On the other hand, by setting the modification rate of maleic anhydride to polyolefin to 5% or less, the insulating layer 130 can be stably formed.

[0143] The content of the maleic anhydride-modified polyolefin in the resin composition is not particularly limited, but is, for example, 1 part by mass or more and 10 parts by mass or less when the total content of the (A) component and the (B) component is 100 parts by mass. By making the content of the maleic anhydride-modified polyolefin 1 part by mass or more, the compatibility between the base resin (A) and the copolymer (C) is improved, and the copolymer (C) can be uniformly dispersed. On the other hand, by making the content of the maleic anhydride-modified polyolefin 10 parts by mass or less, the insulating layer 130 can be stably molded.

[0144] According to the first modification, the base resin (A) further contains maleic anhydride modified polyethylene, so that the total content of maleic anhydride units in the entire insulating layer 130 can be further increased. In addition, the base resin (A) further contains maleic anhydride modified polyethylene, so that the compatibility between the copolymer (C) containing maleic anhydride units and the base resin (A) can be improved. This allows the maleic anhydride to be uniformly dispersed in the insulating layer 130. As a result, the local accumulation of space charge in the insulating layer 130 can be stably suppressed.

[0145] [Variation 2] In the second modification, the resin composition may further contain a small amount of an inorganic filler to the extent that clogging of the mesh does not occur during the extrusion step.

[0146] Examples of the inorganic filler include at least one of magnesium oxide (MgO), silicon dioxide, zinc oxide, aluminum oxide, titanium oxide, zirconium oxide, carbon black, and a mixture of two or more of these.

[0147] The method for forming magnesium oxide includes, for example, a gas phase method in which Mg vapor is brought into contact with oxygen, or a seawater method in which magnesium oxide is formed from seawater as a raw material. The method for forming the inorganic filler in this embodiment may be either the gas phase method or the seawater method.

[0148] Examples of silicon dioxide include at least one of fumed silica, colloidal silica, precipitated silica, and deflagration silica. Among these, fumed silica is preferred as silicon dioxide.

[0149] In this modification, the content of the inorganic filler in the resin composition is, for example, less than 1 part by mass when the total content of the (A) component and the (B) component is taken as 100 parts by mass. By making the content so small, clogging of the mesh during the extrusion process can be suppressed.

[0150] In this modified example, the lower limit of the content of the inorganic filler is not limited as long as the inorganic filler can be added.

[0151] In this modification, the volume average particle size (MV: Mean Volume Diameter) (X described below) of the inorganic filler is not particularly limited, but is, for example, 1 μm or less, preferably 700 nm or less, and more preferably 100 nm or less.

[0152] The "volume average particle size (MV)" here refers to the particle size of the particles di , the volume of the particle V i Then, it can be calculated by the following formula: MV = Σ(V i d i ) / ΣV i The volume average particle size is measured using a dynamic light scattering particle size / particle size distribution measuring device.

[0153] The lower limit of the volume average particle diameter of the inorganic filler is not particularly limited. However, from the viewpoint of stably forming the inorganic filler, the volume average particle size of the inorganic filler is, for example, 1 nm or more, and preferably 5 nm or more.

[0154] In this modification, at least a part of the inorganic filler may be surface-treated with a silane coupling agent, which can improve the adhesion at the interface between the inorganic filler and the base resin, and can improve the mechanical properties and insulating properties of the insulating layer 130.

[0155] According to the second modification, the resin composition further contains a small amount of an inorganic filler, which makes it possible to stably obtain the effect of improving the insulation properties of the insulating layer 130 while suppressing clogging of the mesh during the extrusion process.

[0156] <Other embodiments of the present disclosure> Although the embodiments of the present disclosure have been specifically described above, the present disclosure is not limited to the above-described embodiments and can be modified in various ways without departing from the spirit and scope of the present disclosure.

[0157] In the above-mentioned embodiment and modification, the case where the base resin (A) contains a polyolefin and the case where the base resin (A) further contains a maleic anhydride-modified polyolefin are described, respectively, but the resin composition may contain a copolymer of an olefin and a polar monomer as the base resin (A) in addition to these. Examples of the copolymer of an olefin and a polar monomer include an ethylene-ethyl acrylate (ethylene-ethyl acrylate) copolymer, an ethylene-methyl acrylate copolymer, an ethylene-butyl acrylate copolymer, an ethylene-methyl methacrylate copolymer, and an ethylene-glycidyl methacrylate copolymer. Two or more of these may be used in combination.

[0158] In the above-described embodiment and modified examples, the resin composition contains an additive such as a crosslinking agent, and the insulating layer 130 is crosslinked by the crosslinking agent. However, the insulating layer 130 does not have to be crosslinked.

[0159] In particular, when the base resin (A) contains polypropylene, the insulating layer 130 may be non-crosslinked. In this case, even if the insulating layer 130 is non-crosslinked, it can satisfy the insulating properties required for the power cable 10. Furthermore, since the insulating layer 130 is non-crosslinked, the insulating layer 130 can be recycled.

[0160] When the base resin contains polypropylene, it is preferable that the styrene-based elastomer (B) contains at least one of a propylene unit and a butylene unit among the above-mentioned materials, for example, so that the compatibility between the base resin (A) and the styrene-based elastomer (B) can be improved. EXAMPLES

[0161] Next, examples according to the present disclosure will be described. These examples are merely examples of the present disclosure, and the present disclosure is not limited to these examples.

[0162] (1) Power cable samples Each of the power cables of the samples A1 to A11 and B1 to B9 was manufactured by the following procedure.

[0163] (1-1) Production of resin composition The following compounding ingredients were mixed in a Banbury mixer and granulated in an extruder to produce a pellet-shaped resin composition.

[0164] [Base resin (A)] Low-density polyethylene (LDPE) (density d = 0.920 g / cm 3 , MFR=1g / 10min, SPM elastic modulus 500MPa): 0 parts by mass or more and 100 parts by mass or less Polypropylene (propylene random polymer, isotactic, density d = 0.900 g / cm 3 , MFR=0.6g / 10min, SPM elastic modulus 1100MPa): 0 or 98 parts by mass Maleic anhydride modified polyethylene (modification rate 0.3%, SPM elastic modulus 500 MPa): 0 or 5 parts by mass

[0165] [Styrene-based elastomer (B)] B1, B2 and B3: hydrogenated styrene butadiene styrene block copolymer (SEBS), respectively (The following are listed in order: B1, B2, B3) Ethylene content in component (B): 20% by mass, 37% by mass, 44% by mass Styrene content in component (B): 65% by mass, 40% by mass, 30% by mass SPM elastic modulus of component (B): 50MPa, 300MPa, 100MPa (B) Component content: 0 parts by mass or more and 30 parts by mass or less

[0166] The total content of the components (A) and (B) was taken as 100 parts by mass.

[0167] [Copolymer (C)] C1 and C2: styrene-maleic anhydride copolymer (glass transition temperature: 115°C) Others: Styrene-maleic anhydride-allyl ether copolymer (glass transition temperature: 115°C) Styrene content of C1 and C2: 75% by mass, 80% by mass Maleic anhydride content of C1 and C2: 25% by mass, 20% by mass SPM elastic modulus of C1 and C2: 1500MPa, 1300MPa (C) component content: 0 parts by mass or more and 20 parts by mass or less The maleic anhydride content of the styrene-maleic anhydride-allyl ether copolymer is 25% by mass.

[0168] The above-mentioned "SPM elastic modulus" refers to the elastic modulus measured by SPM. The elastic modulus was measured by SPM at 25°C under the condition that a cantilever having a tip made of silicon with a curvature radius of less than 20 nm was tapped 60,000 times within a 10 μm square area of ​​the polyolefin.

[0169] [Other additives] (Inorganic filler) Material: Vapor-phase magnesium oxide (MgO) (volume average particle size: 50 nm) Inorganic filler content: 0 to 2 parts by weight

[0170] (Antioxidants) Material: Phenolic antioxidant (4,4′-thiobis(3-methyl-6-t-butylphenol)) Antioxidant content: 0 parts by mass or more and 0.3 parts by mass or less

[0171] (lubricant) Material: Fatty acid amide Lubricant content: 0 parts by mass or more and 0.01 parts by mass or less

[0172] (Crosslinking agent) Material: Organic peroxide (2,5-dimethyl-2,5-di(tert-butylperoxy)hexane) Crosslinking agent content: 0 parts by mass or more and 1.5 parts by mass or less

[0173] (1-2) Manufacturing of power cable samples Next, a conductor was prepared by twisting together conductor core wires made of dilute copper alloy with a diameter of 14 mm. After the conductor was prepared, the resin composition for the internal semiconductive layer containing an ethylene-ethyl acrylate copolymer, the resin composition for the insulating layer prepared in (1-1) above, and the resin composition for the external semiconductive layer made of the same material as the resin composition for the internal semiconductive layer were respectively fed into extruders A to C. The extrudates from extruders A to C were guided to a common head, and the internal semiconductive layer, the insulating layer, and the external semiconductive layer were simultaneously extruded from the inside to the outside around the conductor. At this time, the thicknesses of the internal semiconductive layer, the insulating layer, and the external semiconductive layer were set to 1 mm, 14 mm, and 1 mm, respectively. Thereafter, the above-mentioned extrusion molded product was heated at about 250°C to crosslink the resin composition for the insulating layer. As a result, a sample of a power cable having a conductor, an internal semiconductive layer, an insulating layer, and an external semiconductive layer from the center to the periphery was produced.

[0174] By the above steps, power cable samples A1 to A11 and B1 to B9 having different resin compositions were manufactured.

[0175] (2) Evaluation The following evaluations were carried out for each of the power cable samples A1 to A11 and B1 to B9. The "resin pressure increase rate" described below was evaluated during the extrusion process of the insulating layer.

[0176] [Sample processing] For each of the power cable samples A1 to A11 and B1 to B9, the insulation layer was thinly sliced ​​from the outer periphery at a position within 100 m from the initial extrusion position of the insulation layer. Next, a sheet of insulation layer having a thickness of 0.20 mm was formed from the center of the insulation layer in the thickness direction. At this time, multiple sheets were formed from approximately the same circumference.

[0177] In the evaluation of the insulation in the longitudinal direction described later, a total of 10 sheets were taken by taking sheets at 10 locations in the insulation layer at intervals of 100 m along the length of the conductor. At each location, a sheet was taken from the center in the thickness direction.

[0178] [Space charge characteristics] The amount of space charge accumulation was determined by the current integral charge method described above. Specifically, a DC electric field of 50 kV / mm was continuously applied to each sample at a temperature of 90°C, and the amount of charge Q 300 The spatial charge accumulation amount (%) was calculated from the above formula based on the charge amount Q0 immediately after application (0 seconds). The evaluation was performed as follows: A (best) when the spatial charge accumulation amount was 25% or less, B (good) when the spatial charge accumulation amount was more than 25% and less than 100%, and C (bad) when the spatial charge accumulation amount was more than 100%.

[0179] [Volume resistivity] The above-mentioned insulating layer sheet was immersed in silicone oil at a temperature of 90°C, and a direct current electric field of 50 kV / mm or 75 kV / mm was applied to the insulating layer sheet using a flat electrode with a diameter of 25 mm, to measure the volume resistivity. 16 A (best) is rated as A (best) when the volume resistivity is 1×10 15 Ω cm or more 1×10 16 If the volume resistivity is less than 1×10 15 If it was less than Ω·cm, it was rated as C (poor).

[0180] [DC breakdown strength] The above-mentioned insulating layer sheet was immersed in silicone oil at a temperature of 90°C, and a flat electrode with a diameter of 25 mm was used to increase the applied voltage at a rate of 4 kV / min. When the insulating layer sheet reached dielectric breakdown, the applied voltage was divided by the sheet thickness to obtain the DC breakdown strength of the insulating layer sheet. When the DC breakdown strength was 200 kV / mm or more, it was evaluated as A (best), when the DC breakdown strength was 160 kV / mm or more but less than 200 kV / mm, it was evaluated as B (good), and when the DC breakdown strength was less than 160 kV / mm, it was evaluated as C (poor).

[0181] [Heat deformation rate] In accordance with JIS C3005, the thermal deformation rate of the sheet of the insulating layer 130 was measured under conditions of a temperature of 120°C and a load of 2 kg. A thermal deformation rate of 40% or less was rated as A (good), and a thermal deformation rate of more than 40% was rated as B (poor).

[0182] [Extrusion stability: resin pressure rise rate] In the above-mentioned extrusion process of the insulating layer, the resin pressure increase rate was measured. At this time, the resin pressure increase rate was the ratio (%) of the resin pressure after 2 hours to the initial resin pressure. When the resin pressure increase rate was 1% or less, it was rated as A (good), and when the resin pressure increase rate was more than 1%, it was rated as B (bad).

[0183] [Extrusion stability: insulation in the longitudinal direction] As described above, the DC breakdown strength was measured for each of the 10 sheets taken at 10 locations on the insulating layer at a given interval along the length of the conductor, under the same measurement conditions as those described in the above [DC breakdown strength]. That is, the DC breakdown strength is the electric field strength at which the sheet undergoes dielectric breakdown when a DC electric field is applied at a temperature of 90°C. From these results, it is possible to determine the {(E MAX -E MIN ) / E AVE The rate of variation (%) of DC breakdown strength was calculated by multiplying the rate of variation (%) by 100. The rate of variation of DC breakdown strength was 20% or less, and was evaluated as A (good), and the rate of variation of DC breakdown strength was more than 20%, and was evaluated as B (poor).

[0184] (3) Results The evaluation results of the power cable samples are shown in Tables 1 and 2 below. In Tables 1 and 2, the unit of the content of the compounding ingredients is "parts by mass." "Ratio of component (B) / component (C)" means the ratio of the content of component (B) to the content of component (C).

[0185] [Table 1]

[0186] [Table 2]

[0187] (Sample B6) In sample B6, which does not contain the styrene-based elastomer (B), copolymer (C), or inorganic filler, the amount of space charge accumulation and volume resistivity measured under a DC electric field of 50 kV / mm, as well as the DC breakdown strength, were all poor. It is believed that the insulation properties of sample B6 were reduced because it did not contain a material that suppresses the local accumulation of space charge.

[0188] (Sample B8) In sample B8, which does not contain the styrene-based elastomer (B), copolymer (C) and inorganic filler but does contain maleic anhydride-modified polyethylene, the amount of space charge accumulation and the volume resistivity measured under a DC electric field of 50 kV / mm, and the DC breakdown strength were each good. However, the amount of space charge accumulation and the volume resistivity measured under a DC electric field of 75 kV / mm, which is a more severe condition, were each poor. In sample B8, it is considered that the total content of polar groups in the composition could not be sufficiently secured, and therefore the local accumulation of space charge could not be suppressed under severe conditions.

[0189] (Sample B9) Sample B9, which does not contain styrene-based elastomer (B) and copolymer (C) but does contain inorganic filler, showed good results in terms of insulation. However, the resin pressure rise rate during the extrusion process and the rate of change in DC breakdown strength along the length of the cable were poor. It is believed that the insulation of sample B9 varied along the length of the cable because the mesh became clogged due to the aggregation of inorganic filler during the extrusion process of the insulation layer.

[0190] (Samples B1 and B4) In sample B1, in which the content of copolymer (C) was less than 0.5 parts by mass, and sample B4, which did not contain copolymer (C), the total content of maleic anhydride units in the composition was less than 0.1 parts by mass. These samples had good DC breakdown strength, but the space charge accumulation amount and volume resistivity measured under a DC electric field of 50 kV / mm were poor. In samples B1 and B4, it is believed that the total content of maleic anhydride units in the composition could not be sufficiently ensured, and therefore the maleic anhydride units could not trap space charges sufficiently.

[0191] (Samples B3 and B5) The DC breakdown strength was good for sample B3, in which the content of the styrene-based elastomer (B) was less than the content of the copolymer (C) (i.e., the ratio of the (B) component / the (C) component was less than 1), and sample B5, which did not contain the styrene-based elastomer (B). However, the space charge accumulation amount and the volume resistivity measured under a DC electric field of 50 kV / mm were poor for sample B5. On the other hand, although the insulation of sample B3 was slightly improved, the space charge accumulation amount and the volume resistivity measured under a DC electric field of 75 kV / mm were both poor. In samples B3 and B5, the styrene-based elastomer (B) could not be sufficiently interposed in the base resin (A), and the copolymer (C) could not be uniformly dispersed. It is considered that this is the reason why the local accumulation of space charge could not be suppressed.

[0192] (Sample B2) In sample B2, in which the content of copolymer (C) was 20 parts by mass or more, the insulation property was good, but the heat deformation rate was poor. In sample B2, it is considered that the contribution of the styrene unit in copolymer (C) to the deformation was large, so that the insulation layer was easily deformed at high temperatures.

[0193] (Sample B7) In sample B7, which contains a styrene-maleic anhydride-allyl ether copolymer as copolymer (C), the amount of space charge accumulation and volume resistivity measured under a DC electric field of 50 kV / mm, as well as the DC breakdown strength, were all poor. In sample B7, the allyl ether in copolymer (C) was eliminated and decomposed during the extrusion or crosslinking process, generating low molecular weight components. For this reason, the low molecular weight components accumulated locally as space charge. It is believed that this resulted in a decrease in insulation properties.

[0194] (Samples A1 to A11) Samples A1 to A11 satisfied the requirements for the content of copolymer (C), the total content of maleic anhydride units in the composition, and the side chains of copolymer (C). The results for Samples A1 to A11 showed that the space charge accumulation amount, volume resistivity, and DC breakdown strength measured under DC electric fields of 50 kV / mm and 75 kV / mm were good. The thermal deformation rate was also good. Furthermore, the resin pressure rise rate in the extrusion process and the rate of variation of DC breakdown strength along the length of the cable were also good.

[0195] In the samples A1 to A11, the content of the copolymer (C) was set to 0.5 parts by mass or more, so that the total content of the maleic anhydride units in the composition was set to 0.1 parts by mass or more. This enabled the maleic anhydride units to adequately trap space charges. As a result, it was confirmed that the insulating layer was able to withstand high voltage even at high temperatures.

[0196] Among these, samples A1 to A3 in which the content of copolymer (C) was 4 parts by mass or more had the best space charge accumulation amount and volume resistivity measured under the condition of a direct current electric field of 75 kV / mm.

[0197] In the samples A1 to A3, the total content of the maleic anhydride units in the composition was 0.8 parts by mass or more. This enabled the maleic anhydride units to stably trap space charges. As a result, it was confirmed that more stable insulation properties were obtained.

[0198] In samples A1 to A11, it was confirmed that the copolymer (C) did not contain side chains that were eliminated by thermal decomposition or hydrolysis at 300° C. or less, and thus the accumulation of space charge in the low molecular weight component could be suppressed.

[0199] In the samples A1 to A11, the content of the copolymer (C) was set to less than 20 parts by mass, which reduced the contribution of the styrene unit in the copolymer (C) to deformation. As a result, it was confirmed that the deformation of the power cable at high temperatures could be suppressed.

[0200] In the samples A1 to A10, the content of the inorganic compound (inorganic filler) in the composition was less than 0.01 parts by mass, which enabled the prevention of clogging of the mesh during the extrusion process of the insulating layer. As a result, it was confirmed that the variation in the insulating properties in the length direction could be suppressed.

[0201] On the other hand, it was confirmed that sample A11, which contains less than 1 part by mass of inorganic filler, is able to stably obtain the effect of improving the insulation properties of the insulating layer while suppressing clogging of the mesh during the extrusion process.

[0202] In sample A9, the total content of maleic anhydride units could be increased by further including maleic anhydride-modified polyethylene in the base resin (A). As a result, it was confirmed that the local accumulation of space charge could be stably suppressed.

[0203] <Preferred aspects of the present disclosure> Preferred aspects of the present disclosure are described below.

[0204] (Appendix 1) A base resin (A) containing a polyolefin; A styrene-based elastomer (B) containing styrene units; a copolymer (C) containing styrene units and maleic anhydride units; having the content of the copolymer (C) is 0.5 parts by mass or more when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass; The content of the styrene-based elastomer (B) is equal to or greater than the content of the copolymer (C); The copolymer (C) does not contain a side chain that is eliminated by thermal decomposition or hydrolysis at 300° C. or less. Resin composition.

[0205] (Appendix 2) A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer includes a resin composition having a base resin (A) containing a polyolefin, a styrene-based elastomer (B) containing a styrene unit, and a copolymer (C) containing a styrene unit and a maleic anhydride unit; the content of the copolymer (C) in the insulating layer is 0.5 parts by mass or more when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass; The content of the styrene-based elastomer (B) in the insulating layer is equal to or greater than the content of the copolymer (C); The copolymer (C) does not contain a side chain that is eliminated by thermal decomposition or hydrolysis at 300° C. or less. Power cable.

[0206] (Appendix 3) The total content of the maleic anhydride units in the insulating layer is 0.1 parts by mass or more when the combined content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. 2. A power cable as defined in claim 2.

[0207] (Appendix 4) A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer includes a resin composition having a base resin (A) containing a polyolefin, a styrene-based elastomer (B) containing a styrene unit, and a copolymer (C) containing a styrene unit and a maleic anhydride unit; a total content of the maleic anhydride units in the insulating layer is 0.1 parts by mass or more when the combined content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass; The content of the styrene-based elastomer (B) in the insulating layer is equal to or greater than the content of the copolymer (C); The copolymer (C) does not contain a side chain that is eliminated by thermal decomposition or hydrolysis at 300° C. or less. Power cable.

[0208] (Appendix 5) The copolymer does not contain any ester, ether, amide, urethane or siloxane linkages. 5. The power cable according to any one of claims 2 to 4.

[0209] (Appendix 6) The volume resistivity of the insulating layer measured under conditions of a temperature of 90° C. and a DC electric field of 75 kV / mm was 1.0×10 15 Ω cm or more 10. The power cable according to claim 2,

[0210] (Appendix 7) The amount of space charge accumulation in the insulating layer sheet measured under conditions of a temperature of 90°C and a DC electric field of 75 kV / mm is 100% or less. 7. The power cable according to any one of appendix 2 to appendix 6.

[0211] (Appendix 8) The content of the copolymer (C) is less than 20 parts by mass when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. 8. The power cable according to any one of appendices 2 to 7.

[0212] (Appendix 9) The thermal deformation rate of the insulating layer measured under conditions of a temperature of 120°C and a load of 2 kg is 40% or less. 10. The power cable according to claim 7 or 8.

[0213] (Appendix 10) The content of the inorganic compound contained in the insulating layer is less than 0.01 parts by mass when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. 10. The power cable according to any one of claims 2 to 9.

[0214] (Appendix 11) The insulating layer further contains an inorganic filler in an amount of less than 1 part by mass when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass. 10. The power cable according to any one of claims 2 to 9.

[0215] (Appendix 12) The insulating layer satisfies the following formula (1) for the rate of variation of DC breakdown strength: (E MAX -E MIN ) / E AVE ≦0.2 (1) However, the DC breakdown strength is the electric field strength at the time when a DC electric field is applied to each of a plurality of sheets taken from a plurality of locations of the insulating layer at predetermined intervals in the longitudinal direction of the conductor at a temperature of 90° C. and the sheet undergoes dielectric breakdown; E MAX , E MIN and E AVE are the maximum, minimum and average DC breakdown strengths of the sheets, respectively. 12. The power cable according to claim 10 or 11.

[0216] (Appendix 13) The glass transition temperature of the copolymer (C) is 110° C. or higher. 13. The power cable according to any one of claims 2 to 12.

[0217] (Appendix 14) The glass transition temperature of the copolymer (C) is 140° C. or less. 14. The power cable according to any one of claims 2 to 13.

[0218] (Appendix 15) The elastic modulus of the polyolefin measured by a scanning probe microscope is 200 MPa or more and 2000 MPa or less. 15. The power cable according to any one of claims 2 to 14.

[0219] (Appendix 16) The elastic modulus of the styrene-based elastomer (B) measured by a scanning probe microscope is 10 MPa or more and 200 MPa or less. 16. The power cable according to any one of claims 2 to 15.

[0220] (Appendix 17) The base resin (A) further contains a maleic anhydride-modified polyolefin. 17. The power cable according to any one of claims 2 to 16.

[0221] (Appendix 18) The base resin comprises polyethylene, The styrene-based elastomer (B) contains an ethylene unit. 18. The power cable according to any one of appendix 2 to appendix 17.

[0222] (Appendix 19) A step of preparing a resin composition having a base resin (A) containing a polyolefin, a styrene-based elastomer (B) containing a styrene unit, and a copolymer (C) containing a styrene unit and a maleic anhydride unit; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, the content of the copolymer (C) in the resin composition is 0.5 parts by mass or more when the total content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass; The content of the styrene-based elastomer (B) in the resin composition is equal to or greater than the content of the copolymer (C); The copolymer (C) is a material that does not contain a side chain that is eliminated by thermal decomposition or hydrolysis at 300° C. or less. A method for manufacturing power cables.

[0223] (Appendix 20) A step of preparing a resin composition having a base resin (A) containing a polyolefin, a styrene-based elastomer (B) containing a styrene unit, and a copolymer (C) containing a styrene unit and a maleic anhydride unit; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, a total content of the maleic anhydride units in the resin composition is 0.1 parts by mass or more when the combined content of the base resin (A) and the styrene-based elastomer (B) is 100 parts by mass; The content of the styrene-based elastomer (B) in the resin composition is equal to or greater than the content of the copolymer (C); The copolymer (C) is a material that does not contain a side chain that is eliminated by thermal decomposition or hydrolysis at 300° C. or less. A method for manufacturing power cables. [Explanation of symbols]

[0224] 10 DC power cable 110 Conductor 120 Inner semiconducting layer 130 Insulating layer 140 Outer semiconducting layer 150 Shielding layer 160 Sheath

Claims

1. a base resin comprising a polyolefin or a polyolefin and a maleic anhydride-modified polyolefin; a styrene-based elastomer containing styrene units and not containing maleic anhydride units; a copolymer containing styrene units and maleic anhydride units in the main chain; having the content of the copolymer is 0.5 parts by mass or more and less than 20 parts by mass when the total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer is equal to or greater than the content of the copolymer; The copolymer does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300° C. Resin composition.

2. A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer comprises a resin composition having a base resin made of polyolefin or a base resin made of polyolefin and maleic anhydride modified polyolefin, a styrene-based elastomer containing styrene units but not maleic anhydride units, and a copolymer containing styrene units and maleic anhydride units in its main chain; a content of the copolymer in the insulating layer is 0.5 parts by mass or more and less than 20 parts by mass when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer in the insulating layer is equal to or greater than the content of the copolymer; The copolymer does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300° C. Power cable.

3. The total content of the maleic anhydride units in the insulating layer is 0.1 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass.

3. The power cable according to claim 2.

4. A conductor; an insulating layer provided so as to cover the conductor; Equipped with the insulating layer comprises a resin composition having a base resin made of polyolefin or a base resin made of polyolefin and maleic anhydride modified polyolefin, a styrene-based elastomer containing styrene units but not maleic anhydride units, and a copolymer containing styrene units and maleic anhydride units in its main chain; a content of the copolymer in the insulating layer is less than 20 parts by mass when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; a total content of the maleic anhydride units in the insulating layer is 0.1 parts by mass or more when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; the content of the styrene-based elastomer in the insulating layer is equal to or greater than the content of the copolymer; The copolymer does not contain side chains that are eliminated by thermal decomposition or hydrolysis at temperatures below 300° C. Power cable.

5. The copolymer does not contain any ester, ether, amide, urethane or siloxane linkages. The power cable according to any one of claims 2 to 4.

6. The volume resistivity of the insulating layer measured under conditions of a temperature of 90° C. and a DC electric field of 75 kV / mm was 1.0×10 15 Ω cm or more 6. The power cable according to claim 2 .

7. The amount of space charge accumulation in the insulating layer measured under conditions of a temperature of 90° C. and a DC electric field of 75 kV / mm is 100% or less. The power cable according to any one of claims 2 to 6.

8. The thermal deformation rate of the insulating layer measured under conditions of a temperature of 120° C. and a load of 2 kg is 40% or less. A power cable according to any one of claims 2 to 7.

9. The content of the inorganic compound contained in the insulating layer is less than 0.01 parts by mass when the total content of the base resin and the styrene-based elastomer is 100 parts by mass. A power cable according to any one of claims 2 to 8.

10. The insulating layer further contains an inorganic filler in an amount of less than 1 part by mass when the total content of the base resin and the styrene-based elastomer is 100 parts by mass. A power cable according to any one of claims 2 to 8.

11. The insulating layer satisfies the following formula (1) for the rate of variation of DC breakdown strength: (E MAX -E MIN ) / E AVE ≦0.2 ・・・(1) However, the DC breakdown strength is the electric field strength at the time when a DC electric field is applied to each of a plurality of sheets taken from a plurality of locations of the insulating layer at predetermined intervals in the longitudinal direction of the conductor at a temperature of 90° C., and the sheet undergoes dielectric breakdown; E MAX , E MIN and E AVE are the maximum, minimum and average DC breakdown strengths of the sheets, respectively.

11. The power cable according to claim 9 or 10.

12. The glass transition temperature of the copolymer is 110° C. or higher. A power cable according to any one of claims 2 to 11.

13. The glass transition temperature of the copolymer is 140° C. or less. A power cable according to any one of claims 2 to 12.

14. The content of the maleic anhydride unit in the copolymer is 10% by mass or more and 50% by mass or less. A power cable according to any one of claims 2 to 13.

15. The content of the styrene unit in the copolymer is 50% by mass or more and 90% by mass or less. A power cable according to any one of claims 2 to 14.

16. The styrenic elastomer further comprises an ethylene unit, The content of the ethylene unit in the styrene-based elastomer is 10% by mass or more and 50% by mass or less.

16. A power cable according to any one of claims 2 to 15.

17. The content of the styrene-based elastomer in the insulating layer is 40 parts by mass or less when the total content of the base resin and the styrene-based elastomer is 100 parts by mass.

17. A power cable according to any one of claims 2 to 16.

18. The copolymer is a styrene-maleic anhydride copolymer.

18. A power cable according to any one of claims 2 to 17.

19. A step of preparing a resin composition having a base resin made of polyolefin or a base resin made of polyolefin and maleic anhydride modified polyolefin, a styrene-based elastomer containing styrene units but not maleic anhydride units, and a copolymer containing styrene units and maleic anhydride units in the main chain; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, a content of the copolymer in the resin composition is 0.5 parts by mass or more and less than 20 parts by mass when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; The content of the styrene-based elastomer in the resin composition is equal to or greater than the content of the copolymer, The copolymer is a material that does not contain side chains that are eliminated by thermal decomposition or hydrolysis at 300° C. or less. A method for manufacturing power cables.

20. A step of preparing a resin composition having a base resin made of polyolefin or a base resin made of polyolefin and maleic anhydride modified polyolefin, a styrene-based elastomer containing styrene units but not maleic anhydride units, and a copolymer containing styrene units and maleic anhydride units in the main chain; forming an insulating layer using the resin composition so as to cover an outer periphery of a conductor; Equipped with In the step of preparing the resin composition, a content of the copolymer in the resin composition is less than 20 parts by mass when a total content of the base resin and the styrene-based elastomer is 100 parts by mass; a total content of the maleic anhydride units in the resin composition is 0.1 parts by mass or more when the total content of the base resin and the styrene-based elastomer is 100 parts by mass; The content of the styrene-based elastomer in the resin composition is equal to or greater than the content of the copolymer, The copolymer is a material that does not contain side chains that are eliminated by thermal decomposition or hydrolysis at 300° C. or less. A method for manufacturing power cables.

Citation Information

Patent Citations

  • Resin composition for electrical insulation

    JP1995149959A

  • Electric insulating composition and electric wire-cable

    JP1996339717A

  • Electric insulating composite, and wire and cable

    JP1998064338A

  • Direct current power cable

    JP1999016421A

  • Olefinic resin composition, method for producing the same and electric cable coated therewith

    JP2002212354A